Public health care staff during the COVID-19 pandemic: a comparison of job demands and work functioning between temporary and permanent staff - Ylse van Dijk; Sarah I. M. Janus; Michiel R. de Boer; Sytse U. Zuidema; Sijmen A. Reijneveld; Corne A. M. Roelen (BMC, 2024)
Abstract Background The COVID-19 pandemic posed an enormous challenge on the public health workforce, leading to the hiring of much temporary staff. Temporary staff may experience poorer working conditions compared to permanent staff. From a public health perspective, we need to know how working conditions are experienced when there is an acute pressure on recruiting sufficient public health care staff. This study aimed to investigate differences in job demands and work functioning between temporary and permanent public health care staff, during the fourth wave of the COVID-19 pandemic in the Netherlands and compare it with available pre-pandemic data from the general working population. Methods This cross-sectional study included temporary (n = 193) and permanent (n = 98) public health care staff from a municipal health care service in the north of the Netherlands. The participants completed a questionnaire with items about quantitative, cognitive, emotional demands (Copenhagen PsychoSOcial Questionnaire, COPSOQ, range 1-100) and work functioning (Work Role Functioning Questionnaire, WRFQ, range 1-100). The participants' scores were compared to the general working population and differences between temporary and permanent staff were investigated using linear regression analysis. In addition, explorative analyses were conducted with temporary staff stratified by task and permanent staff by department. Results Permanent staff had relatively high scores on job demands compared to the general working population, whereas temporary staff had relatively low scores. On work functioning, permanent staff had similar scores as the general working population and temporary staff had better scores. Compared to permanent staff, temporary staff had lower, i.e. better, scores on quantitative (regression coefficient (B)=-26.7; 95% Confidence Interval (CI) -30.8 to -22.5), cognitive (B=-24.4; 95% CI -29.0 to -19.9), and emotional demands (B=-11.8; 95% CI -16.0 to -7.7), and better scores on work functioning (B = 7.8; 95% CI 4.5 to 11.3). Conclusions Temporary staff experienced lower job demands and reported better work functioning than permanent staff. The acute expansion of the public health workforce did not seem to negatively impact the job demands and work functioning of temporary public health care staff.